PROFIL FUNGSI KOGNITIF PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS - Noor Alia Susianti,* Astuti,** Ahmad Asmedi,** Abdul Gofir,** Bambang Djarwoto*** (Neurona Majalah Kedokteran Neuro Sains, 2015)
INTRODUCTION COGNITIVE FUNCTION IMPAIRMENT IS FREQUENTLY PRESENT IN CHRONIC KIDNEY DISEASE CKD PATIENTS WHO ARE UNDERGOING HEMODIALYSIS CURRENT RESEARCH ON COGNITIVE IMPAIRMENT AMONG HEMODIALYSIS PATIENTS SHOWSVARYING RESULTS